Kotelna spalující zemní plyn - Hosnedl, Pavel (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2012)
Diplomová práce se zabývá problematikou stanovení provozních a bezpečnostních rizik plynové kotelny administrativní budovy o celkovém výkonu 4×49 kW. Kotelna je osazena čtyřmi kotli Geminox THRi 10-50. Cílem diplomové práce je stanovení možných rizik provozu a bezpečnosti provozu plynové kotelny. Diplomová práce je rozdělena do několika částí, přičemž v první části je rozebrána stávající situace, včetně teoretických poznatků o rizicích a jejich analýze. V této části jsou nastíněna možná řešení pro identifikaci a kvantifikaci rizik hrozící v plynové kotelně. V další části jsou stanoveny konkrétní rizikové faktory, je provedena jejich analýza pomocí diagramu příčin a následků a metody FMEA. V závěrečné části jsou navržena konkrétní opatření pro vybraná rizika.

This master thesis deals with problems of determining operational and safety risks at gas boiler room in office building with total output of 4×49 kW. The gas boiler room is equipped with four boilers Geminox THRi 10-50. The aim of this master thesis is to determine the potential operational and safety risks of gas boiler room. The master thesis is divided into several parts, when the first part is describing the current situation with some theoretical knowledge and risk analysis. This part also outlines possible solutions for identification and quantification of risks to the gas boiler room. The specific risk factors are determined at other part of master thesis and there is also their analysis, which is solved by cause and effect diagram and by Failure Mode and Effect Analysis. The specific precautions are suggested for chosen risks in final part of master thesis.
Gas fired boiler house
Keywords: Analýza rizik; plynová kotelna; riziko; zemní plyn.; Risk analysis; gas boiler room; risk; natural gas.